PENGARUH PENGGUNAAN MEDIA VIDEO PEMBELAJARAN TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA MATA PELAJARAN IPA KELAS VIII DI SMPN 3 KINALI - Vini Lovita; Abna Hidayati; Mutiara Felicita Amsal; Rahmi Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the impact of instructional video media on student motivation and learning outcomes in science subjects, specifically the human respiratory system, for eighth-grade students at SMPN 3 Kinali. The background of the problem lies in the low motivation and academic performance of students due to the conventional teaching methods commonly used, which often rely only on textbooks and simple PowerPoint slides. This quasi-experimental study employed a Randomized Control Group Posttest-Only Design involving two classes, with class VIII.1 as the experimental group and class VIII.2 as the control group. Data were collected using questionnaires and tests and analyzed using normality, homogeneity, and t-tests. The findings indicate a significant improvement in both motivation and learning outcomes in the experimental group. Based on t-tests, results showed significance levels of 14.38 > 2.001 (motivation) and 4.03 > 2.001 (learning outcomes), confirming that instructional videos significantly enhance students' motivation and academic achievement.